The consequences of information institutional implications of technological change - Kallinikos, Jannis (Edward Elgar, 2006)
This important book addresses the organizational and economic implications of the new technologies of information and communication. Jannis Kallinikos analyses the recent spectacular growth of information and the self-propelling processes through which technological information is increasingly generated out of the reshuffling and recombination of available and interoperable information sources. He argues that information is no longer simply a resource but a pervading element of socio-economic life that is crucially involved in the redefinition of a variety of organizational practices and modes of economic action
Includes bibliographical references and index
Keywords: Organisationswandel; Information; Information technology / Management; Business enterprises / Computer networks